2001
DOI: 10.1104/pp.010318
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Induced Changes in Antioxidative Systems, Hydrogen Peroxide Content, and Differentiation in Scots Pine Roots

Abstract: To investigate whether Cd induces common plant defense pathways or unspecific necrosis, the temporal sequence of physiological reactions, including hydrogen peroxide (H 2 O 2 ) production, changes in ascorbate-glutathione-related antioxidant systems, secondary metabolism (peroxidases, phenolics, and lignification), and developmental changes, was characterized in roots of hydroponically grown Scots pine (Pinus sylvestris) seedlings. Cd (50 m, 6 h) initially increased superoxide dismutase, inhibited the systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
139
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 656 publications
(179 citation statements)
references
References 48 publications
13
139
0
8
Order By: Relevance
“…The biosynthetic capacity of AsA is impaired under severe stress conditions because the AsA pool is generally determined by its rates of not only regeneration but also synthesis (Song et al 2005). It has been reported that regeneration of AsA under Cd stress is insufficient or that AsA synthesis is lower than AsA catabolism (Schützendübel et al 2001(Schützendübel et al , 2002Chao et al 2010). Importantly, both proline and betaine-supplemented seedlings maintained significantly higher AsA content as compared to the seedling treated Cd alone.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthetic capacity of AsA is impaired under severe stress conditions because the AsA pool is generally determined by its rates of not only regeneration but also synthesis (Song et al 2005). It has been reported that regeneration of AsA under Cd stress is insufficient or that AsA synthesis is lower than AsA catabolism (Schützendübel et al 2001(Schützendübel et al , 2002Chao et al 2010). Importantly, both proline and betaine-supplemented seedlings maintained significantly higher AsA content as compared to the seedling treated Cd alone.…”
Section: Discussionmentioning
confidence: 99%
“…Cd has been demonstrated to inactivate or denature proteins by binding to sulfhydryl groups, which causes cellular damages by displacing cofactors from a variety of proteins, including transcription factors and enzymes (Goyer, 1997;Sharma et al, 2000;Schützendübel et al, 2001;Lin and Aarts, 2012). Moreover, Cd also induces oxidative stress, which in turn mediates cellular damage in various plants and animals (Shim et al, 2009;Gallego et al, 2012).…”
mentioning
confidence: 99%
“…Visible symptoms of Cd injury in plants often include leaf chlorosis and necrosis, the discoloration of leaf blades, browning of the root tips, and finally death (Sanità di Toppi and Gabbrielli, 1999). Root browning is reported to be due to the enhanced suberization or lignification of the root tips, and a consequent loss in nutrient uptake capacity (Schützendübel et al, 2001). In this study, the supply of Cd to Mn-starved plants had negative effects on plant growth, accompanied by strong reductions in leaf chlorophylls, with the roots turning a brownish colour.…”
Section: Discussionmentioning
confidence: 55%
“…Increases in MDA caused by Cd exposure have been widely observed (Sandalio et al, 2001;Schützendübel et al, 2001). In the present work, supplying Cd led to increased MDA root concentrations in both Mn-supply treatments, but only in the shoots of plants grown without Mn (Figure 2).…”
Section: Discussionmentioning
confidence: 96%